2021
DOI: 10.1080/09699260.2021.1887589
|View full text |Cite
|
Sign up to set email alerts
|

Lean in, don’t step back: The views and experiences of patients and carers with severe mental illness and incurable physical conditions on palliative and end of life care

Abstract: Clinical Scholar and his research interests lie in health care inequalities, improving equity and accessibility in health care, particularly in relation to the physical healthcare needs of people with mental ill health and learning disabilities. His methodological specialisms lie in arts-based research methods, co-creation and participatory methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(71 citation statements)
references
References 15 publications
0
67
0
Order By: Relevance
“…97 It has long been acknowledged that stigma and prejudicial attitudes are experienced by those living with severe mental illness, 98 reflected in the recent launching of a Lancet commission in this area. 99 Supporting other work in this area 13,95,100,101 this review has shown that stigma and discrimination remain major problems for people with severe mental illness at the end-of-life, especially for those who are homeless. In the case of staff working in end-of-life services stigmatising and prejudicial attitudes towards people with severe mental illness, and particularly people who are homeless, can affect decision-making.…”
Section: Partnershipmentioning
confidence: 80%
“…97 It has long been acknowledged that stigma and prejudicial attitudes are experienced by those living with severe mental illness, 98 reflected in the recent launching of a Lancet commission in this area. 99 Supporting other work in this area 13,95,100,101 this review has shown that stigma and discrimination remain major problems for people with severe mental illness at the end-of-life, especially for those who are homeless. In the case of staff working in end-of-life services stigmatising and prejudicial attitudes towards people with severe mental illness, and particularly people who are homeless, can affect decision-making.…”
Section: Partnershipmentioning
confidence: 80%
“…People living with SPMI have increased somatic risks, higher cancer mortality rates [ 42 ], poorer clinical outcomes [ 43 ], and die significantly earlier due to factors attributable to their mental illnesses. These factors include the side effects of psychotropic medications, unhealthy lifestyles [ 38 ], alcohol and other drug use, poor health monitoring [ 44 , 45 , 46 ], and reduced health prevention and screening, leading to under-detection and late diagnosis of disease [ 18 , 22 , 25 , 26 , 39 , 40 , 45 , 46 , 47 , 48 ]. People with SPMI are particularly vulnerable to shorter life expectancy [ 40 , 49 ] as they are often victims of violence [ 50 ], healthcare system neglect [ 25 , 45 ], and can be excluded from mainstream service support due to barriers such as homelessness [ 26 , 27 , 51 ], cultural insensitivity [ 52 ], poverty, and stigmatisation [ 5 , 14 , 15 , 17 , 18 , 21 , 22 , 24 , 25 , 26 , 27 , 39 , 47 , 49 , 51 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fear of discrimination due to past experiences of stigma often leads people with SPMI to disconnect from services and supports [ 49 ], resulting in unmet needs across a range of areas, including mental and physical healthcare, housing, and alcohol and other drugs (AOD) treatment. In addition, this fear of discrimination can lead to ambivalence regarding receiving treatment and end-of-life and palliative care [ 14 , 21 , 22 , 26 , 39 , 51 , 56 ]. There is, however, across the research ample confirmation that people with SPMI are almost universally stigmatised within health and palliative care settings, resulting in substantial inequity, unmet need, reduced access to care, and poor end-of-life outcomes [ 5 , 14 , 15 , 18 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 39 , 49 , 51 , 53 , 54 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations